Communicationless Adaptive Control Strategy for Effective Reactive Power Sharing in a Grid-Independent AC Microgrid - D, Suchitra; D, Anitha; S, George Fernandez; Alaas, Zuhair Muhammed; Ali, Ziad M.; Abdel Aleem, Shady H. E. (Frontiers in Energy Research, 2022)
The Microgrid (MG) ensures a reliable power supply as it can work in grid-independent mode. This mode requires a coordinated control strategy among Distributed Generators (DGs). One major challenge in a grid-independent MG is the reactive power sharing issue, as it is affected by the mismatch of feeder impedance and private loads. This paper proposes a proportionate reactive power sharing among DGs in grid-independent mode by mathematically computing the equivalent impedance without the need for communication lines. A mathematical formula is derived to compute the equivalent impedance as a function of the total power output of DG and the power fed to the feeder. Based on the equivalent impedance the virtual impedance is added to each feeder. The inclusion of virtual impedance provides accurate reactive power sharing among DGs. MATLAB Simulink is used to verify the effectiveness of the proposed control strategy. Also the real-time OPAL-RT simulator is used to verify the results.